Colic in horses: Effects of dietary factors - Şevket Evci (Turkish Journal of Agriculture: Food Science and Technology)
Studies on colic, an economically important metabolic disease in horses, have typically emphasized maintenance characteristics. However, recent research has demonstrated that nutrient content also contributes to the development of colic. Microbial fermentation of the diet begins in the stomach and continues through the hindgut. During this process, various substrates are produced, including acetate, propionate, butyrate, and methane. The gut contains bacteria such as Firmicutes and Bacteroidetes, but the dominance of one over the other is influenced by the type of substrate available in the gut, such as oat, barley, wheat, corn, etc. Microbial fermentation in the equine cecum is markedly influenced by the pH balance of the nutrient metabolism. This has varying impacts on the cecal microbiota. Investigations into the effects of different feeding methods and nutrients have yielded diverse outcomes for the etiology of colic and post-colic nutrition. The objective of this review is to assess the impact of nutrition and diet composition on the etiology of colic in horses, investigate the role of additives in preventing colic cases, and analyze the results of several studies.